2009
DOI: 10.1007/s12663-009-0057-0
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular third molar and inferior alveolar canal

Abstract: For IAN we found Patient's age, the development of roots, the degree of impaction and the radiographic position of the nerve canal to be significantly correlated to sensory deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(33 reference statements)
2
4
1
Order By: Relevance
“…The pain may be due to the type of impaction, or any pathological growth or condition 1,35 . Similar results showed in the study conducted by Seidu A Bello et al 2011 , and Nagaraj T et al 2016 36,32 . In our study nearly 11.82% of the population had a history of Diabetes mellitus and hypertension etc .…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The pain may be due to the type of impaction, or any pathological growth or condition 1,35 . Similar results showed in the study conducted by Seidu A Bello et al 2011 , and Nagaraj T et al 2016 36,32 . In our study nearly 11.82% of the population had a history of Diabetes mellitus and hypertension etc .…”
Section: Resultssupporting
confidence: 86%
“…This supports the assertion that there are sex-specific mandibular traits with the sexual dimorphism , clearly observed with bigger jaw bone in males 31 . Similarly , the study conducted by Nagaraj T et al 2016, reported that males had higher impaction than females 32 . But contradictory result was found in the study conducted by Korener et al 2015 , stated that the possibility of dietary influence on the physique , role of genetic factors or a combination of genetic and dietary factors have been proposed to have effect on low prevalence of unerupted / impacted third molar this may be the reason for fewer number of males presented compared to females 33,34 .…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…1 The impacted third molars unless surgically removed are retained throughout the life -time of a person and are thus prone to further complications like pericoronitis, cyst and tumor formation from the developmental remnants, neuralgic pain related to the inferior alveolar canal impingement, alteration in occlusion, masticatory dysfunction, and temporomandibular joint disorders in the long run. 2 Removal of the impacted third molars is considered prophylactically or when associated with pathology. Deferring the procedure is related to comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…6 The Inferior Alveolar Nerve runs in ID (Inferior Dental) canal which is usually near to apices of mandibular third molar, if third molars are impacted so their roots are present close to nerve. 7,8 On routine clinical examination impacted mandibular third molar are commonly seen and they are in close relation to the lingual and inferior alveolar nerve, during surgical extraction these nerves can be damaged. 5,9,10 In a literature review seven radiographic indicators of a close relationship between inferior dental canal and impacted third molar are observed , four signs are seen in the root of tooth (darkening, deflection, narrowing and bifid root apex) and the other three are seen in inferior dental canal (diversion, narrowing and interruption in the canal).…”
Section: Introductionmentioning
confidence: 99%